Second Five Year Plan Bombay State Sabarkantha District - Government of Bombay (Government of Bombay, 1959)
The Second Five-Year Plan (1959–1965) for Sabarkantha District in the former Bombay State presents a comprehensive strategy for socio-economic development aimed at improving agricultural productivity, infrastructure, education, healthcare, and social welfare across the district. Covering an area of approximately 2,845 square miles with a population of 684,017 distributed across 1,778 villages, the district faced significant developmental challenges due to its geographical features, including the Aravali hills and limited irrigation resources, as well as a substantial population of scheduled tribes and other backward communities. The plan places primary emphasis on agricultural development through improved farming practices, enhanced seed distribution, fertilizer use, land reforms, and expanded irrigation facilities through tanks, wells, and bandharas to irrigate nearly 94,650 acres. Livestock development is promoted through improved veterinary services, establishment of veterinary dispensaries, and vaccination programs to control diseases such as rinderpest. Forestry initiatives focus on afforestation, conservation of natural forests, establishment of nurseries, and promotion of medicinal plant cultivation to support environmental sustainability and local economic activities. Industrial development strategies emphasize the promotion of cottage and village industries, including handloom and leather work, along with the establishment of cooperative societies and industrial cooperatives to strengthen rural economic self-sufficiency and improve access to agricultural and artisan financing through cooperative banking systems. Infrastructure development constitutes another major component, particularly the expansion and improvement of road networks, including the development of National Highway 8 and construction of bridges and transport facilities to enhance connectivity and support trade and agricultural marketing. The plan also records significant progress in the expansion of educational facilities, with a substantial increase in the number of primary and secondary schools since 1948, along with initiatives to make primary education free and compulsory, establish teacher training colleges, introduce vocational and multipurpose secondary education, and promote technical and skill-based learning. Healthcare improvements include the expansion of medical institutions, establishment of cottage hospitals, strengthened vaccination programs, and anti-malaria campaigns aimed at improving public health conditions. Additionally, housing initiatives for low-income families, slum clearance programs, and targeted welfare measures for backward classes, including scholarships, financial support, and training programs, are integral parts of the plan. Through integrated community development and National Extension Services, the plan seeks to uplift marginalized populations, enhance economic opportunities, and improve overall living standards, thereby laying the foundation for long-term sustainable development in Sabarkantha District.
Sabarkantha District
Sabarkantha District
Keywords: State Five Year Plan; Sabarkantha District Development; Agricultural Development Programs; Minor Irrigation Projects; Animal Husbandry Services; Forestry and Afforestation; Cottage and Village Industries; Infrastructure and Road Development; Educational Expansion Programs; Public Health and Disease Control; Welfare for Backward Classes; Community Development and National Extension Services